1987
DOI: 10.1007/bf00331162
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of DNA fragments complementary to tobacco nitrate reductase mRNA and encoding epitopes common to the nitrate reductases from higher plants

Abstract: Messenger RNAs encoding the nitrate reductase apoenzyme from tobacco can be translated in a cell-free system. Poly(A)+ mRNA fractions from the 23-32 S area of a sucrose gradient were used to build a cDNA library in the expression vector gt11 with an efficiency of cloning of approximately 10(4) recombinants/ng mRNA. Recombinant clones were screened with a rabbit polyclonal antibody directed against the corn nitrate reductase, which cross reacts specifically with the nitrate reductases from dicotyledons. Among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 38 publications
2
66
0
1
Order By: Relevance
“…10 and references therein). It has been shown for both NR in several plant species (5,7,9) and for NiR in spinach and maize (3,16) (2,8).…”
Section: Expression Of Nir Mrna In the Presence Of Ammoniamentioning
confidence: 96%
See 3 more Smart Citations
“…10 and references therein). It has been shown for both NR in several plant species (5,7,9) and for NiR in spinach and maize (3,16) (2,8).…”
Section: Expression Of Nir Mrna In the Presence Of Ammoniamentioning
confidence: 96%
“…The seedlings were grown hydroponically by floating the foam pads on the surface ofthe media. Two salt media were used: (a) minimal medium, 10 mM Mes (pH 5.5), 5 mM CaSO4; (b) complete medium (minus nitrogen), 5 For RNA blot hybridization, 20 ,g of leaf or 10 ,ug of root total cellular RNA was subjected to electrophoresis through a 1.2% agarose, 2.2 M formaldehyde gel, and the RNA was blotted onto nitrocellulose. The probe used for the hybridization was a NiR cDNA insert from the plasmid pCIB801 (16).…”
Section: Plant Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent progress in cloning cDNA for NR3 demonstrated that steady state levels ofNR transcripts were increased by nitrate induction in the light (3,8,9). For corn leaves, application of nitrate to N-starved, etiolated seedlings in the dark led to small increases in NR protein and activity, but large increases were found when light was given (15).…”
mentioning
confidence: 99%